Every business is a growth business how your company can prosper year after year - Charan, Ram; Tichy, Noel M. (John Wiley & Sons, 1999)
This text argues that sustained growth can be achieved through a way of thinking. the author's provide a framework that is based on five keys, including: there's no such thing as a mature business; and not all growth is good.